2014
DOI: 10.1111/bjh.12887
|View full text |Cite
|
Sign up to set email alerts
|

Minimal residual disease monitoring in chronic lymphocytic leukaemia patients. A comparative analysis of flow cytometry and ASO IgH RQPCR

Abstract: SummaryMinimal residual disease (MRD) is becoming increasingly important in chronic lymphocytic leukaemia (CLL) as treatment strategies are progressively improving. The primary objective of this study was to compare the applicability of three different flow cytometric approaches: basic 4-colour analysis, European Research Initiative in CLL (ERIC) consensus method and 8-colour analysis. Secondly, we investigated the sensitivity and specificity of flow cytometry (FC) compared to molecular analyses for MRD detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 24 publications
3
33
0
Order By: Relevance
“…The study by Raponi et al22 conducted a comparative analysis of FLC and real-time ASO-PCR for MRD monitoring in CLL. This was done by monitoring blood and bone marrow samples from 98 patients, establishing a consensus of 82% between the two methods.…”
Section: Comparison Of Methods For Mrd Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study by Raponi et al22 conducted a comparative analysis of FLC and real-time ASO-PCR for MRD monitoring in CLL. This was done by monitoring blood and bone marrow samples from 98 patients, establishing a consensus of 82% between the two methods.…”
Section: Comparison Of Methods For Mrd Detectionmentioning
confidence: 99%
“…Raponi et al22 also addressed this question and found an approximately 92% concordance between results in bone marrow and PB; however, among the discordant 8% almost all were positive in bone marrow and negative in PB, implying that true MRD negativity cannot be unequivocally determined using PB only.…”
Section: Comparison Of Methods For Mrd Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stehlíková et al and Raponi et al suggested an 8-color labeling antibodies methodology application for the FC in order to enhance detection of MRD as well as to reduce the difficulties associated with the preparation of samples for laboratory analysis [17,35]. Stehlíková has used the regime with two tubes which seems to be easier and less time-consuming then 4-color labeling method utilizing 4 tubes.…”
Section: Mrd Evaluation Using 8-color Labeling Antibodies For Flow Cymentioning
confidence: 99%
“…Another difficulty is the necessity of designing PCR primers for each patient. Raponi et al have taken into consideration the direct sequencing of DNA before designing primers for ASO IGH RQ-PCR reaction [35]. This approach is expensive, and the validation of the method for the implementation to the daily clinical practice is extremely difficult.…”
Section: Mrd Evaluation Using Aso Igh Rq-pcr Techniquementioning
confidence: 99%